2002
DOI: 10.1046/j.1432-1033.2002.03135.x
|View full text |Cite
|
Sign up to set email alerts
|

Altering the surface properties of baculovirus Autographa californica NPV by insertional mutagenesis of the envelope protein gp64

Abstract: The envelope protein gp64 of the baculovirus Autographa californica nuclear polyhedrosis virus is essential for viral entry into insect cells, as the glycoprotein both mediates pHdependent membrane fusion and binds to host cell receptors. Surface modification of baculovirus particles by genetic engineering of gp64 has been demonstrated by various strategies and thus has become an important and powerful tool in molecular biology. To improve further the presentation of peptides on the surface of baculovirus part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
1
22
0
1
Order By: Relevance
“…AcV1, another monoclonal antibody against an epitope extensively overlapping with the heparin-binding region, does not inhibit virus binding to the cell surface (41). Lastly, this heparinbinding region can tolerate insertions of and substitutions by a variety of foreign sequences without affecting virus titers, suggesting that the heparin-binding function is dispensable for infection of Sf9 cells (10,37,51). Our results for the effects of GT24 and heparin on virus infectivity also support this hypothesis.…”
Section: Discussionsupporting
confidence: 72%
“…AcV1, another monoclonal antibody against an epitope extensively overlapping with the heparin-binding region, does not inhibit virus binding to the cell surface (41). Lastly, this heparinbinding region can tolerate insertions of and substitutions by a variety of foreign sequences without affecting virus titers, suggesting that the heparin-binding function is dispensable for infection of Sf9 cells (10,37,51). Our results for the effects of GT24 and heparin on virus infectivity also support this hypothesis.…”
Section: Discussionsupporting
confidence: 72%
“…A multiplex influenza-coated suspension array could be used to detect and quantify relevant virus-specific antibody titers in patient blood and to subtype influenza virus infections. Moreover, fusing existing recombinant baculoviral HIV-1 gp120 surface libraries (16,27 ) to our composite could facilitate a more precise and reliable determination of early-phase HIV infections.…”
Section: Discussionmentioning
confidence: 99%
“…In the baculoviral vector system this site was previously described for the introduction and surface display of peptides ranging in size from 6 to 12 amino acids, with the resulting baculovirus particles having an approximately 5-fold reduction in viral infectivity compared with GP64 (Ernst et al, 2000;Spenger et al, 2002). Characterization of the PreS1-GP64 protein showed that it was indeed expressed and resulted in surface display of the PreS1 peptide as determined by immunostaining and flow cytometric measurements ( Fig.…”
Section: Figmentioning
confidence: 99%
“…At present, the structure of GP64 has not yet been determined, the domains of the protein involved in cell binding have not been characterized, and the mammalian cell receptor(s) or general cell surface motifs used for cell binding have not been described (Duisit et al, 1999;Tani et al, 2001;Ghosh et al, 2002). Because previous reports of peptide insertions into the GP64 envelope protein did not show alteration of baculoviral tropism (Ernst et al, 2000;Spenger et al, 2002) and because no modifications were made to ablate the native tropism, the observed loss in gene transfer to HeLa cells was not expected. This suggests that insertion of the PreS1 peptide may alter the structure of the GP64 protein, in particular the domains involved in recognizing mammalian cell surface molecules, as the PreS1-GP64 protein appears to retain other functions (Fig.…”
Section: Figmentioning
confidence: 99%